ANALISIS ALAT BUKTI YANG SAMA DALAM PERKARA PIDANA YANG BERBEDA (STUDI KASUS SETYA NOVANTO DALAM PUTUSAN PRAPERADILAN PENGADILAN NEGERI JAKARTA SELATAN NOMOR: 97/PID.PRAP/2017/PN.JKT.SEL) - Alnan Marchelita Pradewi; Firman Wijaya (Fakultas Hukum Universitas Tarumanagara, 2018)
Evidence is the important instrument to decide criminal cases and Its began from investigation, prosecution, until court decisions. Evidence is arrange in article 184 and explanation of KUHAP. Police investigating to determine someone be a suspect or unknown through investigation about entanglement according to evidence any goods and the evidence available. In fact many law enforcement officials such as police used power revenue and their authority to quickly resolve the cases with no accordance to the procedure. Therefore to minimize those things law enforcement need supervision as pretrial. Pretrial have authority to judge about legal or failure arrest, detention termination investigation or termination prosecution; compensation and or rehabilitation for criminal cases stopped at the investigation or prosecution. Related to the verdict of South Jakarta District Court number 97/Pid.prap/2017/Pn.Jkt.Sel, judge Cepi Iskandar said that the same evidence cannot be used as evidence in other criminal cases brought many different polemics. Generally judge decide on criminal cases based to article 183 KUHAP and in fact many criminal cases was using the same evidence especially to cases with more than one defendant or participation cases. Judge Cepi Iskandar decision have given uncertainty law in the public, so it needs analysis and further discussion about the evidence and the consideration on that judicial decisions.